Climate risk disclosure and financial performance of high carbon emission companies in China - Norman Mohd Saleh; Duan Shuang (Penerbit Universiti Kebangsaan Malaysia, 2024)
Unlike past studies that focus on environment, social and governance disclosure, this study aims to examine the association between climate risk disclosure (CRD) and corporate financial performance (FP). Climate-related risks are fundamentally intertwined with a company's risks, amplifying the drive for companies to communicate these risks to stakeholders openly. This study used a sample of 1,241 annual reports of China's high carbon emission A-share listed companies from 2013 to 2022 as samples and used the climate-related risk keywords developed by prior literature to quantitatively measure the level of the company's disclosure of climate risk information. The empirical results indicate that CRD, which is directly related to the overall business risks, is positively associated with the three FP measurement indicators, i.e., return on assets, return on equity and Tobin’s Q. The results also passed the robustness tests. Theoretically, the results underscore the importance of stakeholder legitimacy actions in the form of CRD because it informs stakeholders' decisions and empowers them to support sustainable business practices that could enhance company performance.